Relative toxicity of benzodiazepines and hypnotics commonly used for self-poisoning: An epidemiological study of fatal toxicity and case fatality. (June 2018) - Geulayov, Galit; Ferrey, Anne; Casey, Deborah; Wells, Claudia; Fuller, Alice; Bankhead, Clare; Gunnell, David; Clements, Caroline; Kapur, Navneet; Ness, Jennifer; Waters, Keith; Hawton, Keith
The relative toxicity of anxiolytic and hypnotic drugs commonly used for self-poisoning was assessed using data on suicides, prescriptions and non-fatal self-poisonings in England, 2005–2012. Data on suicide by self-poisoning were obtained from the Office for National Statistics, information on intentional non-fatal self-poisoning was derived from the Multicentre Study of Self-harm in England and data on prescriptions in general practice from the Clinical Practice Research Datalink. We used two indices of relative toxicity: fatal toxicity (the number of fatal self-poisonings relative to the number of individuals prescribed each drug) and case fatality (the number of fatal relative to non-fatal self-poisonings). Diazepam was the reference drug in all analyses. Temazepam was 10 times (95% confidence interval 5.48–18.99) and zopiclone/zolpidem nine times (95% confidence interval 5.01–16.65) more toxic in overdose than diazepam (fatal-toxicity index). Temazepam and zopiclone/zolpidem were 13 (95% confidence interval 6.97–24.41) and 12 (95% confidence interval 6.62–22.17) times more toxic than diazepam, respectively (case-fatality index). Differences in alcohol involvement between the drugs were unlikely to account for the findings. Overdoses of temazepam and zopiclone/zolpidem are considerably more likely to result in death than overdoses of diazepam. Practitioners need to exercise caution when prescribing these drugs, especially for individuals who may be at risk of self-harm, and also consider non-pharmacological options.